Markers of bone turnover across a competitive season in female athletes: a preliminary investigation - Morgan, A. L.; Weiss Jarrett, J. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: Higher levels of bone formation have been observed in athletes performing high impact exercise when compared to non-impact exercisers. This study was designed to determine if bone formation and resorption fluctuate across a competitive season (4-6 months) in females training at different levels of mechanical stress. METHODS: Markers of bone formation (osteocalcin [OC]; bone specific alkaline phosphatase [BAP]) and resorption (cross-linked N-telopeptides [NTx]) were measured in serum at pre-, mid- and post-season in 33 female athletes and controls (19.6±1.4 yr). Participants were divided into impact groups of high (HIGH, basketball, N.=6), medium (MED, soccer, N.=12), and non (NON, swimmers, N.=11), and compared to sedentary controls (CON, N.=4). Bone mineral density (BMD) and bone mineral content (BMC) were assessed by DXA in a subset of each group. RESULTS:BAP was greater in HIGH and MED (31.82±12.21 and 33.09±6.78 U/L) than both NON and CON (23.96±5.71 and 16.66±2.07 U/L); no significant changes over time were noted. Hip BMD was greater in HIGH (1.17±0.14 g×cm-2) than NON and CON (0.98±0.09 and 1.02±0.04 g×cm-2, respectively), while hip BMC was greater in HIGH and MED (41.76±3.06 and 38.56 ± 3.94 g) than NON and CON (32.37 ±3.5 and 30.51 ± 5.91). CONCLUSION:Women involved in HIGH and MED impact activities have higher levels of bone formation throughout a season than those involved in non-impact activities which may have long term implications for bone health.